Chain Writing Sebagai Inovasi Pembelajaran Menulis Di SD Kelas Rendah - Desi Apriani; Qory Amalia; Tri Diani (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
essay is something that can help children to develop their ideas or imaginations. However, in learning to write there are problems that often occur, namely, the lack of motivation of students and teachers. Less effective and innovative writing learning methods are also the cause of not developing students writing skills. One of the things that can affect the success of write learning is innovation. The innovation that can be used for learning to write story essay is chain writing. With the chain writing, write learning can be more fun, attractive and innovative. This study uses a descriptive qualitative approach. Literary descriptive qualitative research is an activity related to collectinglibrary data, reading, recording and processing research materials. This study discusses whether the chain writing method is effective in writing skills in low grades and how to apply chain writing. From the results that have been described in the article, the chain writing method is considered effective for learning writing skills in lower grade elementary schools. There is also the application of chain writing learning innovation. In this application, students are asked to take turns writing in groups, with a theme or clue in the form of a picture that has been determined by the teacher. From the theme or picture, students are asked to make a story essay. Incorporating a game into learning is one of the innovations that can make learning interesting and not boring. Chain writing has a goal that all students can play an active role in learning, learning is carried out in groups so that students can work together with their peers.